Plant/soil-microbial fuel cell operation effects in the biological activity of bioelectrochemical systems. Issue 2 (15th June 2022) - Valdez-Hernández, Mirna; Acquaroli, Leandro N.; Vázquez-Castillo, Javier; González-Pérez, Omar; Heredia-Lozano, Julio C.; Castillo-Atoche, Alejandro; Sosa-Vargas, Lydia; Osorio-de-la-Rosa, Edith
ABSTRACT: Plant and soil microbial fuel cells (PMFCs and SMFCs, respectively) are bioelectrochemical systems that produce energy using microorganisms as catalysts. This energy can be harvested; however, its impact on biological activity has seldom been explored. To reveal the main characteristics of this impact, we monitored four experimental designs for 20 days under open-sky conditions. The effect of PMFC/SMFC start-up on metabolism was evaluated by photosynthesis of Codiaeum variegatum and heterotrophic soil respiration to determine the short-term effects. To compare the results, a normalized parameter of power density, which considered the PMFC/SMFC configurations, solar irradiance, and soil temperature, was introduced. The highest energy was obtained for the PMFC configuration. The energy harvesting stimulated the photosynthetic rate of C. variegatum up to two times with respect to its normal values, while the heterotrophic soil respiration decreased 30%. Thus, in the PMFC and SMFC start-up operations, the increase in soil temperature due to energy harvesting suggests that soil temperature is the most relevant parameter influencing plant metabolism and energy generation. These results open a new pathway for understanding the bioregulation of plants/soil when subjected to energy harvesting.